If the limit of n → ∞ lim ( sin n + 1 π + sin n + 2 π + sin n + 3 π + sin 2 n π ) = a ln b where a , b are real numbers and b is prime. Find the value or a b + b a .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The given expression can be rewritten as lim n → ∞ ∑ i = 1 n n + i π sin n + i π × n + i π = π lim h → 0 , n h = 1 ∑ i = 1 n 1 + i h h = π ∫ 0 1 1 + x d x = π ln 2 . So, a = π , b = 2 , and a b + b a = π 2 + 2 π ≈ 1 8 . 6 9 4 5 .
Call the limit of sum L ( n ) = n → ∞ lim k = 1 ∑ n sin n + k π . By Taylor theorem one can easily deduce that for x > 0 the following inequality holds true. x − 6 x 3 < sin x < x and for x = n + k π and k > 0 we have n → ∞ lim k = 1 ∑ n ( n + k π − 6 ( n + k ) 3 π 3 ) < L ( n ) < n → ∞ lim k = 1 ∑ n n + k π Also we note that 2 n 1 ≤ n + k 1 ≤ n + 1 1 as n + 1 ≤ n + k ≤ 2 n for 1 ≤ k ≤ n ( prove by induction ) and hence n → ∞ lim 8 n 3 π k = 1 ∑ n ≤ L ′ ( n ) ≤ ( n + 1 ) 3 π n → ∞ lim k = 1 ∑ n therefore the limit of n → ∞ lim k = 1 ∑ n 6 ( n + k ) 3 π = L ′ ( n ) = 0 by squeeze theorem as the n → ∞ lim 8 n 3 π k = 1 ∑ n = n → ∞ lim 8 n 3 n π = 0 = n → ∞ lim ( n + 1 ) 3 π n and hence the original limit (by squeeze theorem) L ( n ) = n → ∞ lim k = 1 ∑ n n + k π = ∫ 0 1 1 + x π d x = π ln 2 and the required answer is π 2 + 2 π ≈ 1 8 . 6 9 4 5 .
Problem Loading...
Note Loading...
Set Loading...
Let us rewrite the series as :- n → ∞ lim r = 1 ∑ n n 1 1 + n r π sin ( n 1 1 + n r π ) ( n 1 ) ( 1 + n 1 π ) 1
Now the sequence n 1 1 + n r π tends to 0 as n → ∞
So let us call it θ = n 1 1 + n r π . Hence θ → 0 as n → ∞ .
So lim n → ∞ ( sin ( n 1 1 + n r π ) ) ( n 1 1 + n 1 π ) 1 = lim θ → 0 θ s i n ( θ ) tends to 1 as n → ∞
So the sum is equivalent to :-
n → ∞ lim r = 1 ∑ n n 1 1 + n r π
Using Riemann Sums , we have:-
∫ 0 1 1 + x π d x = π ln ( 2 )